Interannual summer biodiversity changes in ichthyoplankton assemblages of the Strait of Sicily (Central Mediterranean) over the period 2001–2016 - Patti, Bernardo; Torri, Marco; Cuttitta, Angela (Frontiers in Marine Science, 2022)
Interannual fluctuations in the structure and the composition of ichthyoplankton assemblages in the pelagic waters of the Strait of Sicily (SoS, Central Mediterranean) were investigated, trying to relate them to the observed variability in oceanographic conditions. Plankton data used in this study were from 16 summer surveys carried out in the SoS every year from 2001 to 2016, using oblique bongo plankton net (0–100 m) tows. Out of more than 12,000 fish larvae collected in the sampling stations included in the analysis, 9,519 of them were identified and regularly classified in 15 orders and 49 families. Ichthyoplankton assemblages, defined at the family level due to the uniform availability of this information along the time series, showed a decreasing trend over time in total larval abundance, along with taxonomic (family) richness and Shannon index (α diversity), more pronounced in the shelf area and in the slope area, respectively. Conversely, the relatively high levels of yearly compositional changes observed in the larval assemblage from both shelf and slope areas, as estimated by the Jaccard dissimilarity index (β diversity), did not show any significant linear trend. In addition, a biodiversity hotspot (both in terms of family richness and Shannon index) was evidenced in the frontal structure characterizing the southeastern part of the study area. Generalized additive models were used to evaluate the effect of oceanographic conditions on the temporal and spatial patterns of ichthyoplankton biodiversity. Results evidenced the role of salinity, surface temperature, and surface currents in modulating biodiversity indices, especially in the shelf area. Finally, the relevance of local frontal oceanographic structures in sustaining high biodiversity levels is postulated.